RELATIONSHIP BETWEEN FAMILY SUPPORT AND ANXIETY LEVELS IN CORONARY HEART DISEASE (CHD) CLIENTS AT THE CARDIOLOGY CLINIC OF RSUD HOSPITAL LANGSA - Fitriyani, Irma Hartati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: Cardiovascular disease is the number one cause of death in the world. Family support can help improve an individuals coping mechanisms by providing emotional support and advice on alternalif strategies based on previous experiences. Anxiety is a vague uneasy feeling of discomfort or fear accompanied by a response (the cause is not specific or is unknown to the individual). This study aims to determine the relationship between family support and anxiety levels in clients with coronary heart disease. Methods: This study uses chi square test with analytic design with cross sectional approach and Accidental Sampling technique. Result: There is a relationship between family support and anxiety levels in clients with coronary heart disease with p-value 0.033 (p0.05). Recommendation: Langsa Hospital in order to can improve services for coronary heart disease patients who experience anxiety, especially at the Cardiology Clinic, by providing more sources of information about disease conditions and treatment, as well as holding psychological counseling about their anxiety. In addition, nurses at the Cardiology Polyclinic of Langsa Hospital can improve the quality of nursing care for patients with coronary heart disease who experience moderate and severe levels of anxiety. By taking a supportive approach such as counseling and providing explanations about the disease and anxiety, to improve the patient's coping mechanisms.